TENOLOGI PENGAMBILAN AIR LAUT DENGAN BANGUNAN SUMUR BERPORI PADA WILAYAH BERPASIR DI PESISIR PANTAI BENGKULU - Derry Yumico (Universitas Bengkulu, 2018)
Pondfish maintenance requires sea water supply. To fulfill the required at Pantai Bengkulu coastal representing sandy coastal have the problem not yet fulfilled of quality and quantity the sea water. With the existence at above problem hence conducted a research. The research needed for collected data. Existing data used for scheme base model. Evaluation for the result use existing formula. From scheme result get a model for the region of sandy coastal. For the sandy coastal used well intake are combination concrete buis and pore pipe. The well have diameter 3 m and 6,5 m deepnes. Pore pipe have length 8 m and diameter is 10 cm. From merger of both can be yielded charge 0,27 m3/ second.